Sosialisasi Pembagian Waris Berdasarkan Hukum Islam (Fara’id) Melalui Aplikasi Digital Sebagai Upaya Edukasi Distribusi Kekayaan Berbasis Syariah Di Era Digital: Inheritance Distribution, Islamic Law (Fara’id), Digital Applications, and Wealth Distribution." - Riski, Bagus; Ridwan, Muhammad; Kadariah, Siti; Anugrah, Bima (Publikasi Pengabdian Masyarakat, 2025)
The Inheritance issues frequently become a source of conflict within families, primarily due to the limited understanding among Muslim communities regarding the distribution of inheritance in accordance with Islamic law (fara’id). One of the main obstacles faced is the difficulty in accurately calculating each heir’s rightful share based on Sharia principles. In many cases, confusion also arises even among religious leaders when determining inheritance portions according to Islamic jurisprudence (fiqh). To address this challenge, this community service initiative focused on the socialization of Islamic inheritance distribution through the use of a digital application called “Hitung Waris” (Inheritance Calculator). This application is designed with informative and interactive features, including definitions of inheritance, relevant Quranic and Hadith-based legal foundations, identification of heirs along with their respective rights and conditions, and a simulation for inheritance calculations. The application’s calculation process follows several stages, beginning with input on the deceased (muwarris), total estate (tirkah) including assets, debts, wills, and funeral expenses, followed by identifying the primary heirs, and ultimately presenting the results in accordance with fara’id rules. The socialization activity was conducted on Thursday, May 29, 2025, at Al-Ikhlas Mosque, Pasar 1 Rel, Medan Marelan District, and was attended by the mosque’s Subuh prayer congregation. The evaluation of this activity revealed strong enthusiasm from participants during discussions and Q&A sessions, along with improved understanding of Sharia-compliant inheritance distribution. The digital application proved to be a practical and accurate tool in helping the community understand and calculate inheritance in accordance with Islamic justice principles. Thus, this initiative makes a tangible contribution to promoting literacy in Islamic inheritance law and fair wealth distribution through a technology-based approach in the digital era.